1994
DOI: 10.1177/001872679404700502
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Antecedents of Subjective Career Success Among a Managerial Sample in Singapore

Abstract: Data obtained with a questionnaire instrument from managerial employees (N = 200) in Singapore were used to examine some antecedents of subjective career success. The choice of antecedents was informed by recent calls to place research on career issues in the context of an individual's life roles. Confirmatory factor analysis (LISREL VII) was used to examine the one-factor and three-factor models hypothesized to underlie the subjective career success data. The results revealed a three-factor model to have adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 29 publications
7
137
0
6
Order By: Relevance
“…The people with high levels of work investment are those who focus most on the positive elements of their environment, and who are used to interpreting events as favorably as possible (Lee et al, 1992). Organizations thus tend to offer the best career opportunities to the most committed people, increasing their chances of success (Aryee et al, 1994). Nonetheless, this recognition by the organization takes different forms for men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The people with high levels of work investment are those who focus most on the positive elements of their environment, and who are used to interpreting events as favorably as possible (Lee et al, 1992). Organizations thus tend to offer the best career opportunities to the most committed people, increasing their chances of success (Aryee et al, 1994). Nonetheless, this recognition by the organization takes different forms for men and women.…”
Section: Discussionmentioning
confidence: 99%
“…From the works of Rosenbaum (1989), Aryee, Chay and Tan (1994) and Ng et al (2005), it has identified three well-known approaches that describe about the predictors of career success that are at the individual perspective, the structural perspective and the behavioural perspectives. The first approach mainly spotlights on the individual perspective, which helps an individual to build up his or her own human capital and then capitalises their education and skills investment in order to achieve career success.…”
Section: Career Success and Its Variablesmentioning
confidence: 99%
“…It is the natural expectation of any individual employee to achieve success in his or her career, and their success depends on what an individual expects from it. According to the studies of Poon (2004); Burke (2001), Aryee, Chay and Tan (1994) and Nabi (2000), intrinsic or subjective career success is intangible or less visible indicator such as future career prospects, career satisfaction, perceptions of accomplishments, then career commitment as well as career mentoring, all these internal factors are being considered and evaluated by the individual's own subjective judgement of career success (Table 1). In this research study, career success is given prime importance.…”
Section: Career Success and Its Variablesmentioning
confidence: 99%
“…1, JUNI 2005 Namun demikian, kesuksesan karir tidak hanya diukur dari posisi (jabatan) dan gaji. Kesuksesan karir mengandung dua makna, yaitu sukses karir secara objektif dan subjektif (Jaskolka et al, 1995;Melamed, 1996;Aryee et al, 1994). Kesuksesan karir secara objektif dapat diukur secara mudah seperti posisi kerja dan gaji, sedangkan kesuksesan karir secara subjektif tidak dapat diukur dengan mudah (Nabi, 1999).…”
Section: Pendahuluanunclassified
“…Sementara itu kesuksesan karir secara subjektif merupakan kesuksesan karir yang tidak dapat diukur secara objektif (Nabi, 1999, Judge et al, 1995Pelluchette, 1993;Jaskolka et al, 1985). Kesuksesan karir secara subjektif dapat diartikan sebagai perasaan yang dimiliki oleh seorang pegawai mengenai karirnya, seperti persepsi pencapaian karir dan prospek masa depan karirnya (Aryee et al, 1994). Individu yang memperoleh kesuksesan berkarir secara subjektif akan merasa lebih bahagia dan merasa lebih sukses dalam karir secara relatif walaupun mereka sebenarnya tidak mencapai standar kerja yang seharusnya.…”
Section: Kesuksesan Karirunclassified